DELEGATING DESTRUCTION: PRINCIPAL-AGENT DILEMMAS AND THE POLITICAL ECONOMY OF HEALTH SOVEREIGNTY IN FRAGILE STATES - Bagus Satrio Utomo; Lila Irawati Tjahjo Widuri (Intermestic: Journal of International Studies, 2026)
The traditional “guns versus butter” model fails to capture aid allocation in fragile states where external donors fund both security and social sectors. Using principal-agent theory, we argue that aid modality (budget support versus humanitarian bypass). With the aid of structured comparison and fuzzy-set Qualitative Comparative Analysis (fsQCA) of four states with developed, yet varying, armed conflicts: the Democratic Republic of the Congo (DRC), Afghanistan, Colombia, and Ukraine, I analyze how aid delegation (budget support vs. humanitarian aid) affects the resilience of health systems. Findings suggest that parallel humanitarian aid generates numerous principal-agent problems which produces a sovereignty gap and separate the provision of services from the accountability structures. However, the scope of this is limited. First, budget support builds a state’s capacity only if it is accompanied by middle levels of pre-existing institutionalization (e.g. Colombia, Ukraine). In states that are classified as collapsed (post-2021 Afghanistan and the DRC), aid support might even further predatory extraction. The article connects the literature of liberal peace and delegation theory in International Relations, claiming that the form of international aid is a dependent variable which determines the pathways of state formation. In post-colonial nations, externally placed delegation often repeats the ‘extraversion’ process which undermines the social contract.